Artificial Intelligence in Genebanks: Seed Multispectral Analysis for Germplasm Integrity and Targeted Breeding Traits - Zaher, Oumaima; Choukri, Hasnae; Moulakat, Adil; Tsivelikas, Athanasios; Kehel, Zakaria (2024)
Artificial Intelligence in Genebanks: Seed Multispectral Analysis for Germplasm Integrity and Targeted Breeding Traits.